Health Alliance for Digital Development and Action (HADDA). (30th September 2020) - Elmi, M
Abstract: SPIDER's Digital Health Programme in Somalia - HADDA - supports Somalia's National Plan for health system strengthening through the use of digital tools for data and knowledge sharing. By deploying and tailoring a Health Information Management System for the country's health system, the programme will enhance the capacity of healthcare workers, whilst enabling policy makers to analyse public health data, plan, manage and deliver quality healthcare for all in Somalia. To realise this, a number of Maternal and Child Health Clinics and referral services will be selected that will connect the entire care pathway in Puntland and Galmudug linking them to the Federal Ministry of Health. Based on the outcome of a needs-assessment in the selected regions, the evidence will determine the required digital infrastructure and human resources and skills necessary for the programme to succeed. SPIDER, in alliance with the Somali government authorities, will engage and mobilise key stakeholders, practically adhering to the digital principles for development for the strengthening of the health system. In tandem with the implementation of project activities, SPIDER will support an independent and ongoing research programme to monitor the outcomes of programme. This will help to improve the methods of application, manage risks, and sustain the results.